MANAJEMEN BUDAYA LITERASI MELALUI KEGIATAN APEL PAGI DI MADRASAH ALIYAH NEGERI 3 MANDAILING NATAL - Auliya Nasution, Mursyidan; Sulthan Arrasyid Nasution; Ananda Fahmul Afkar; Ahmad Riadi; Sunanto Nauli; Muharnita Azizah Rangkuti; Tauhid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low national literacy index necessitates innovative managerial re-engineering at the educational unit level to foster a competitive learning ecosystem. This study aims to analyze the management of literacy culture through the "Literacy Strengthening" program integrated into morning assembly activities at Madrasah Aliyah Negeri (MAN) 3 Mandailing Natal. Utilizing a descriptive qualitative approach, data were collected through one month of participatory observation, in-depth interviews with the headmaster, teachers, and students, as well as documentation studies via the madrasah's digital platform. The data were analyzed using an interactive model comprising data reduction, display, and verification. The results indicate that the headmaster performs a strategic role as an instructional leader through a systematic management cycle, including: (1) Participatory planning aligning literacy with the institutional vision; (2) Collaborative organizing with clear role distribution among teachers and students; (3) Consistent implementation through habituation methods, book reviews, and public speaking; and (4) Reflective supervision to maintain program quality. The transformation of the morning assembly from a mere administrative routine into a space for idea articulation is proven effective in enhancing students' self-confidence, public communication skills, and critical thinking. This study concludes that strengthening literacy culture based on institutional routine activities represents a best practice in internalizing "Kurikulum Merdeka" values and the "Profil Pelajar Pancasila," while serving as an acceleration model for human resource quality within the madrasah environment.